Marketing Mix (Product, Price, Promotion, and Location) on Sales Volume of Micro, Small, and Medium Enterprises (MSMEs) in South Sulawesi - Nyamin Sucipto; Otto R. Payangan; Hasrullah Liong Misi (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This study aims to examine the effect of marketing mix elements—product, price, and place—on sales volume among Micro, Small, and Medium Enterprises (MSMEs) in South Sulawesi. It also seeks to provide empirical insights into the role of these factors in supporting firms’ sales performance. Research Design and Methodology: This research adopts a quantitative descriptive approach using secondary data obtained from literature review and company documentation. The data were analyzed using multiple linear regression, preceded by classical assumption tests to ensure the robustness and validity of the model. Findings and Discussion: The findings reveal that product has a negative and significant effect on sales volume, indicating that improvements in product attributes do not necessarily lead to increased sales. Price demonstrates a positive and significant effect, suggesting that appropriate pricing strategies play a crucial role in driving sales performance. Meanwhile, place shows a negative and insignificant effect, implying that location has not yet become a primary determinant in consumers’ purchasing decisions. Implications: This study provides practical implications for business managers to prioritize competitive pricing strategies, reevaluate product management, and improve distribution and promotional systems in a more structured manner to enhance sales volume. Additionally, the findings contribute to the existing literature on marketing mix and MSMEs, particularly in the context of emerging markets.